Quality of the discussion of asthma on twitter. (1st February 2022) - Kaul, Viren; Szakmany, Tamas; Peters, Jay I.; Stukus, David; Sala, Kathleen A.; Dangayach, Neha; Simpson, Steven Q.; Carroll, Christopher L.
Abstract: Introduction Patients obtain a large amount of medical information online. Much of this information may not be reliable or of high quality. We investigated what influences the discussion of asthma on Twitter by evaluating the most popular tweets and the quality of the links shared. Methods We used Symplur Signals to extract data from Twitter examining characteristics of the top 100 most shared tweets and the 50 most shared links that included the hashtag #asthma. Information on each site was assessed using an Asthma Content score, and validated DISCERN scores and HONCode criteria. Results The top 100 asthma-related tweets were shared 10, 169 times and had 16, 044 likes. Healthcare organizations posted 49 of the top 100 tweets, non-healthcare individuals posted 20, non-healthcare organizations posted 16 and clinicians posted 14. Of the top 100 tweets, 62 were educational, 11 research-related, 10 political and 15 promotional. The top 50 links were shared 6009 times (median number of shares 92 per link (range 60-710)). Links most commonly (42%) led to educational content while 24% of links led to research articles, 22% to promotional websites, and 12% to political websites. Educational links had higher Asthma Content scores than other links ( p  < 0.005). Overall, all three scores were low for all types of links. Only 34% of sites met HONCode criteria, and 14% were assessed as high quality by DISCERN score. Conclusion The top tweets using the hashtag #asthma were commonly educational. The majority of top links on Twitter scored poorly on asthma content, quality, and reliability.